Experimental assessment of lamella heat exchanger as cold intake air system for spark ignition engine by utilizing vehicle air conditioning system - Ikhtiar, Usman; Hairuddin, Abdul Aziz; Asarry, Azizan; Md. Rezali, Khairil Anas; Ali, Hafiz Muhammad; Abdul Jalal, Rifqi Irzuan (Elsevier, 2023)
Global warming and air pollution have become major concerns for humanity, especially in the last few decades. The transport sector contributes significantly to a large proportion of urban air pollution due to the dramatic increase in vehicle production and transportation growth, resulting in harmful emissions. Cooling the intake air temperature is one of the alternative strategies to reduce exhaust emissions and improve combustion conditions. The present study adopted the Lamella heat exchanger (LHE) as an intake air cooling device for a 1.5 L naturally aspirated engine. The design size of LHE is based on the maximum space available in the test vehicle for its installation. A refrigerant derived from the vehicle air conditioning (VAC) system acts as a coolant medium for LHE. For experimental testing, two types of vehicle statuses are considered, i.e., moving and static, to evaluate the performance of the cooling device in both positions. Engine power, torque, exhaust emissions, and fuel consumption are designated as evaluating parameters. The results depict that lowering the temperature of the intake air by 30–40 through LHE reduces the increased quantity of exhaust emissions due to the VAC system by 43.6%, 39.5%, 47.3%, and 64.5% for CO, CO2, HC, and NOx respectively. Further, the amount of lost engine power and torque due to the VAC system is partially recovered by 17% and 24%, respectively, by introducing cold air into the engine. Convincingly, LHE has a significant potential to improve engine performance.